SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT IKAN NILA MENGGUNAKAN BAYES - Adi Nugroho, Hermawan; Lusiana, Veronica (Information Technology and Telematics, 2018)
ABSTRACT Tilapia is one type of freshwater fish has been cultivated because of abundant benefits. However, due to the lack of knowledge of farmers about the disease in tilapia resulted in the lack of crops from these fish. Consultation of fish diseases to a specialist of course very reliable, because an expert always mastered the field he was based on the science and experience. The goal to be achieved is to create an expert system application that is useful as a tool to get information in diagnosing tilapia disease. The result of this research is expert system to diagnose tilapia disease using bayes algorithm to solve the problem of tilapia fish disease diagnosis, because it can give diagnosis result with probability value occurrence of each kind of disease.